Penggunaan Website Trademap untuk Mengidentifikasi Potensi Ekspor bagi UMKM - Alfarisy, Muhammad Farid; Wibowo, Arif Andri (Jurusan Ilmu Ekonomi dan Studi Pembangunan | Universitas Jenderal Soedirman, 2024)
The main challenge for business actors is the international market's lack of reliable trade information. Therefore, a data source is needed to provide an overview of the real conditions of world trade. Trademap is a web developed by the International Trade Centre UNCTAD/WTO (ITC) to help business actors facilitate market research. This service aims to introduce the Trademap website to MSME business actors.